Research Progress in Stretchable Circuits: Materials, Methods, and Applications - Xiaojun Pan; Zhangsheng Xu; Rongrong Bao; Caofeng Pan (Advanced Sensor Research, 2023)
Abstract Stretchable electronic devices, with their excellent properties such as stretchability and conformal contact with complex surfaces, are widely used in health monitoring and human‐computer interactions. For stable operation of these devices, stretchable circuits are crucial, enabling integration of sensors, data collection, and transmission while under strain. To achieve stretchable system integration, addressing key issues such as elastic substrates, sensor devices, rigid components, stretchable electrodes, and packaging layers is necessary. The stretchable electrodes, which connect various functional devices, are crucial for achieving stretchability and are the main focus of this review. Firstly, this work explores the enhancement of electrode design to maintain good electrical conductivity even under stretching conditions, through studying stretchable conductive materials and the structural design of conventional materials. This work then presents studies on substrate interfaces and the design of elastic substrates, such as rigid islands, to enhance the stability of stretchable circuits during use. Finally, the article discusses the applications of stretchable circuits, the challenges they face, and provides new research directions and ways to develop stretchable circuits.